Optimising clinician workflow: enhancing efficiency in same-day emergency care (SDEC) - Jayesh Chopra; Yakut Khan; Rajeev Kumar; Shaun Trussell (Future Healthcare Journal, 2025)
Introduction: Same-day emergency care (SDEC) is a relatively new care model under which patients presenting to hospital can be rapidly assessed, diagnosed and treated, thus helping patient flow, reducing acute admissions and improving the overall patient experience.1New doctors rotating through the SDEC department can find it challenging because the workflow differs significantly from their usual shifts and work patterns due to the emphasis on same-day assessment and treatment.A survey questionnaire was designed with eight objective questions and four subjective questions, which was filled out by resident doctors rotating through the SDEC department in our hospital. It identified a lack of familiarity with SDEC protocols, workflow inconsistencies and a clear need for accessible guidance for new staff members. Success of the SDEC model depends on a skilled and confident workforce delivering high-quality patient care.2This quality improvement project was done with the goal of addressing specific workflow bottlenecks and enhancing clinician confidence by the creation of a reference tool for matters relating to clinical practice and workflows in the SDEC department. Methods: After the initial survey questionnaire, feedback was collated. Using the feedback, an SDEC guide was designed, which included comprehensive information about the workings of the SDEC department, covering everything from room code keys, prescribing methods and discharge pathways, to patient flow, among others. Its distribution was facilitated to all resident doctors working within acute and general medicine who rotate through SDEC. The guide was also presented as part of acute medical teaching; for new doctors working in the department, a one-to-one induction and run through were also provided.A post-implementation survey was conducted with a questionnaire containing the same objective and subjective questionnaires, along with two added questions to measure impact and obtain further feedback on the guide tool. Results: The data from the two surveys were compared and showed a significant improvement in not only the knowledge of protocols, but also that clinicians felt more confident while working in the SDEC department. There were 15 responses for the initial survey and 10 responses for the second survey.The results from the objective questions in the two questionnaires are detailed in Table 1 and those from the subjective questions pertaining to clinician comfort are detailed in Table 2.